The reforms in Spanish and Polish public administration in 2010-2015 from the perspective of new public management - Ignacy, Jarosław (Reformy administracji publicznej w Polsce i w Hiszpanii w latach 2010-2015 z perspektywy nowego zarządzania publicznego, 2018)
We have witnessed fundamental changes in developmental conditions in the last decade. Their pace is constantly growing, and the increasing dynamics of socio-economic transformations create a new reality. The consequences of the changes affect not only companies, but also public administration. Therefore, the goal of the article was to identify the directions of the reforms of new public management in Polish and Spanish public administration in the years 2010-2015. An analysis of the research results shows that the most important trends of the reforms in Poland included: i) transparency of actions, ii) digital administration and e-government and iii) cooperation between various entities of the public sector, whereas Spanish respondents regarded the following trends as the most important: i) digital administration and e-government, ii) reduction of the public sector, iii) transparency of actions. The results of the research show the progressive convergence of the directions and tools of the reforms in EU countries, while maintaining differences in some aspects of development in particular countries.
Management Sciences = Nauki o Zarządzaniu, 2018, vol. 23, no. 4; s. 42-47
Keywords: public management; new public management; reforms of public administration in Poland and Spain; strategic management